Selected individual and environmental factors predisposing to Human papillomavirus infections. Part I. Common warts - Samochocki, Zbigniew; Rujna, Paweł; Malejczyk, Magdalena; Majewski, Sławomir (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction. Common warts are the most frequent form of human papillomavirus infections. Clinical observations indicate that, due to changes in environmental factors and behaviours, risk factors for these infections also undergo changes. Objective. To assess how selected predisposing factors affect the prevalence of common warts. Material and methods. The study comprised 340 men, aged 19-26 years, living in a so-called “closed environment” of a military unit. The influence of individual, behavioural and environmental factors on the development of warts was analysed. The subjects were examined twice: before the start of their active military service and after a 6-month follow-up. Results. In the first examination, common warts (mainly on hands) were diagnosed in 9.1% of subjects. The second examination revealed the presence of cutaneous warts in 3.3% of new subjects, mainly on their feet (6/7). The findings confirmed that the main risk factors for developing common warts were familial and individual history of warts, and attendance of swimming pools and solariums. Common warts were statistically more frequently observed in men with coexistent atopic dermatitis, pruritus and xeroderma. Conclusions. The study indicates that individual history of atopic dermatitis, xeroderma and pruritus should be considered as an additional risk factor predisposing to HPV infections, whereas the fact of living in a “closed environment” is lower risk.